Efficacy of cyclin-dependent-kinase 9 inhibitors in a murine model of mixed-lineage leukemia - Garcia-Cuellar, M-P; Füller, Elisa; Mäthner, Emanuel; Breitinger, Constanze; Hetzner, Katrin; Zeitlmann, L.; Borkhardt, A.; Slany, Robert (Leukemia, 2014)
Mixed-lineage leukemia fusion proteins activate their target genes predominantly by stimulating transcriptional elongation. A core component necessary for this activity is cyclin-dependent kinase 9. Here we explored the effectiveness of small molecules targeting this enzyme as potential therapeutics. A screen of seven compounds with anti-CDK9 activity applied to a panel of leukemia cell lines identified flavopiridol and the experimental inhibitor PC585 as superior in efficacy with inhibitory concentrations in the submicromolar range. Both substances induced rapid dephosphorylation of the RNA polymerase II C-terminal domain, accompanied by downregulation of CDK9-dependent transcripts for MYC and HOXA9. Global gene expression analysis indicated the induction of a general stress response program, culminating in widespread apoptosis. Importantly, colony-forming activity in leukemia lines and primary patient samples could be completely inhibited under conditions that did not affect native precursors from bone marrow. In vivo application in a mouse transplant model significantly delayed disease with PC585 showing also oral activity. These results suggest CDK9 inhibition as novel treatment option for mixed-lineage leukemia. © 2014 Macmillan Publishers Limited.
Keywords: CDK9; inhibitor; mixed-lineage leukemia; preclinical study

HOX genes regulate Rac1 activity in hematopoietic cells through control of Vav2 expression - Breitinger, Constanze; Mäthner, Emanuel; Garcia-Cuellar, Maria-Paz; Schambony, Alexandra; Fischer, K. D.; Schilling, K.; Slany, Robert (Leukemia, 2013)

Leukemogenic transformation by HOXA cluster genes - Bach, Christian; Buhl, Sebastian; Mueller, Dorothee; Garcia-Cuellar, Maria-Paz; Mäthner, Emanuel; Slany, Robert (Blood, 2010)
HOX homeobox genes are important regulators of normal and malignant hematopoiesis. Abdominal-type HOXA genes like HOXA9 are highly leukemogenic. However, little is known about transformation by anterior HOXA genes. Here we performed a comprehensive assessment of the oncogenic potential of every HOXA gene in primary hematopoietic cells. With exception of HOXA2 and HOXA5, all HOXA genes caused a block or delay of hematopoietic differentiation and cooperated with Meis1. No evidence for the alleged tumor-suppressor function of HOXA5 could be found. Whereas all active HOXA genes immortalized mixed granulocytic/ monocytic populations, HOXA13 preferentially specified monocytoid development. The anterior HOXA genes HOXA1, HOXA4, and HOXA6 transformed cells, generating permanent cell lines, although they did so less potently than HOXA9. Upon transplantation these lines induced myeloproliferation and acute myeloid leukemia in recipient animals. Kinetic studies with inducible HOX derivatives demonstrated that anterior HOXA genes autonomously contributed to cellular transformation. This function was not mediated by endogenous Hoxa9, which was persistently expressed in cells transformed by anterior HOX genes. In summary our results demonstrate a hitherto unexpected role of anterior HOXA genes in hematopoietic malignancy. © 2010 by The American Society of Hematology.

Misguided transcriptional elongation causes mixed lineage leukemia - Mueller, Dorothee; Garcia-Cuellar, Maria-Paz; Bach, Christian; Buhl, Sebastian; Mäthner, Emanuel; Slany, Robert (Plos Biology, 2009)
Fusion proteins composed of the histone methyltransferase mixed-lineage leukemia (MLL) and a variety of unrelated fusion partners are highly leukemogenic. Despite their prevalence, particularly in pediatric acute leukemia, many molecular details of their transforming mechanism are unknown. Here, we provide mechanistic insight into the function of MLL fusions, demonstrating that they capture a transcriptional elongation complex that has been previously found associated with the eleven-nineteen leukemia protein (ENL). We show that this complex consists of a tight core stabilized by recursive protein-protein interactions. This central part integrates histone H3 lysine 79 methylation, RNA Polymerase II (RNA Pol II) phosphorylation, and MLL fusion partners to stimulate transcriptional elongation as evidenced by RNA tethering assays. Coimmunoprecipitations indicated that MLL fusions are incorporated into this complex, causing a constitutive recruitment of elongation activity to MLL target loci. Chromatin immunoprecipitations (ChIP) of the homeobox gene A cluster confirmed a close relationship between binding of MLL fusions and transcript levels. A time-resolved ChIP utilizing a conditional MLL fusion singled out H3K79 methylation as the primary parameter correlated with target expression. The presence of MLL fusion proteins also kept RNA Pol II in an actively elongating state and prevented accumulation of inhibitory histone methylation on target chromatin. Hox loci remained open and productive in the presence of MLL fusion activity even under conditions of forced differentiation. Finally, MLL-transformed cells were particularly sensitive to pharmacological inhibition of RNA Pol II phosphorylation, pointing to a potential treatment for MLL. In summary, we show aberrant transcriptional elongation as a novel mechanism for oncogenic transformation. © 2009 Mueller et al.

MLL-ENL Inhibits Polycomb Repressive Complex 1 to Achieve Efficient Transformation of Hematopoietic Cells - Mäthner, Emanuel; Garcia-Cuellar, Maria-Paz; Breitinger, Constanze; Takacova, Sylvia; Divoky, Vladimir; Hess, Jay L.; Slany, Robert (Cell Reports, 2013)
Stimulation of transcriptional elongation is a key activity of leukemogenic MLL fusion proteins. Here, we provide evidence that MLL-ENL also inhibits Polycomb-mediated silencing as a prerequisite for efficient transformation. Biochemical studies identified ENL as a scaffold that contacted the elongation machinery as well as the Polycomb repressive complex 1 (PRC1) component CBX8. These interactions were mutually exclusive invitro, corresponding to an antagonistic behavior of MLL-ENL and CBX8 invivo. CBX8 inhibited elongation in a specific reporter assay, and this effect was neutralized by direct association with ENL. Correspondingly, CBX8-binding-defective MLL-ENL could not fully activate gene loci necessary for transformation. Finally, we demonstrate dimerization of MLL-ENL as a neomorphic activity that may augment Polycomb inhibition and transformation. © 2013 The Authors.

The homeodomain region controls the phenotype of HOX-induced murine leukemia - Breitinger, Constanze; Mäthner, Emanuel; Garcia-Cuellar, Maria-Paz; Slany, Robert (Blood, 2012)
HOX proteins are widely involved in hematopoietic development. These transcription factors combine a conserved DNAbinding homeobox with a divergent N-terminus that mediates interaction with variable cofactors. The resulting combinatorial diversity is thought to be responsible for mammalian HOX specificity. Contrasting this proposed mechanism for normal HOX function, here we demonstrate that, in the context of hematopoietic immortalization and leukemogenesis, individual HOX properties are governed almost exclusively by the homeodomain. Swap experiments between HOXA1 and HOXA9, 2 members of nonrelated paralog groups, revealed that gene expression patterns of HOX transformed cells in vitro are determined by the nature of the homeodomain. Similar results were seen in vivo during HOX-mediated leukemogenesis. An exchange of the homeodomains was sufficient to convert the slow, low-penetrance phenotype of HOXA1- induced leukemia to the aggressive fastacting disease elicited by HOXA9 and vice versa. Mutation and deletion studies identified several subregions within the DNAbinding domain responsible for paralog specificity. Previously defined binding sites for PBX cofactors within the exchangeable, nonhomeobox segment were dispensable for in vitro oncogenic HOX activity but affected in vivo disease development. The transcriptional activator domain shared by HOXA1 and HOXA9 at the very N-terminus proved essential for all transformation. © 2012 by The American Society of Hematology.